이산화황이 고추와 가지의 생리적 반응 및 시스테인과 글루타치온 함량에 미치는 영향 - 이현경(Hyun Kyung Lee); 우수영(Su Young Woo); 곽명자(Myeong Ja Kwak); Inkyin Khaine; 김이레(Ie Reh Kim); 이태윤(Tae Yoon Lee); 장지휘(Ji Hwi Jang); 유하나(Ha Na You); 김원일(Won Il Kim) (Weon'ye gwahag gi'sulji, 2018)
이 연구는 시설재배작물로 많이 이용되는 고추와 가지를 대상으로 이산화황(아황산가스, SO2) 노출에 의해 나타나는 광합성률, 수분이용효율, 엽록소 함량 및 형태학적인 변화와 시스테인, 글루타치온의 함량 변화를 구명하기 위하여 수행되었다. 환경조절 챔버에서 SO2를 24시간 동안 50μg·kg-1의 농도로 처리하였다. 대조구와 처리구로 나누어 광합성률, 수분이용효율, 엽록소(chlorophyll) 및 카로티노이드(carotenoid) 함량, 가시적인 피해증상 관찰, 기공 특성과 생화학적 분석(cysteine, glutathion)을 통해 변화를 조사하였다. SO2 처리 후 두 작물 모두에서 광합성량이 감소하였고, 수분이용효율은 증가하였다. 엽록소와 카로티노이드 함량은 두 작물 모두 처리구에서 감소하였다. 가시적인 피해는 고추의 경우 14일째, 가지의 경우 18일째에 처음으로 관찰되었으며 황색 및 백색 반점이 생기고 시간이 지날수록 괴사현상도 발생되었다. 기공 상태는 대조구에 비해 SO2 처리구에서 기공의 크기와 수가 감소하였다. SO2 처리 후 고추와 가지의 생화학적 변화에서는 시스테인과 글루타치온의 함량이 증가하였다. This study was carried out to investigate the photosynthetic rate, water use efficiency, chlorophyllcontent, morphological changes, and cysteine and glutathione contents of pepper and eggplantplants treated with 50 μg·kg-1 sulfur dioxide (SO2) in a controlled environment chamber. Plantswere treated with 50 μg·kg-1 SO2 for 24 h/day in a naturally irradiated phytotron. After exposure,SO2 damage was examined by evaluating photosynthetic rate, water use efficiency (WUE),chlorophyll and carotenoid content, visible injury, stomata characteristics, and cysteine andglutathione content. The photosynthetic rate was significantly lower in treated plants compared tothe control, and WUE increased with the SO2 treatment in both pepper and eggplant compared tountreated plants. The chlorophyll and carotenoid content also decreased in plants treated with SO2. The visible injury to leaves appeared after about 14 d of SO2 exposure in pepper and 18 d after SO2exposure in eggplant. The leaves had yellow and white spots on their surface in both the pepper andeggplant plants. Over a period of SO2 exposure, necrosis was observed in both pepper and eggplantleaves. Stomatal density and size decreased in response to SO2 exposure in both of pepper andeggplant. The cysteine and glutathione levels significantly increased after SO2 exposure in bothpepper and eggplant. KCI Citation Count: 1